2022
DOI: 10.1111/ele.14119
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen enrichment alters multiple dimensions of grassland functional stability via changing compositional stability

Abstract: Anthropogenic nutrient enrichment is known to alter the composition and functioning of plant communities. However, how nutrient enrichment influences multiple dimensions of community‐ and ecosystem‐level stability remains poorly understood. Using data from a nitrogen (N) and phosphorus (P) addition experiment in a temperate semi‐arid grassland that experienced a natural drought, we show that N enrichment, not P enrichment, decreased grassland functional and compositional temporal stability, resistance and reco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
40
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(44 citation statements)
references
References 109 publications
3
40
1
Order By: Relevance
“…Landscape‐level selective logging experiments may provide additional evidence of landscape‐level processes of community assembly and the potential impact on ecological restoration. The effect of anthropogenic disturbance on compositional stability at the local scale has been receiving greater attention in other ecosystems (such as grasslands) (Xu et al 2022, Li et al 2023). Based on our results, embracing the dual nature of ecosystem stability across spatial scales in different taxa will contribute to a better understanding of the overall stability of ecosystems in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Landscape‐level selective logging experiments may provide additional evidence of landscape‐level processes of community assembly and the potential impact on ecological restoration. The effect of anthropogenic disturbance on compositional stability at the local scale has been receiving greater attention in other ecosystems (such as grasslands) (Xu et al 2022, Li et al 2023). Based on our results, embracing the dual nature of ecosystem stability across spatial scales in different taxa will contribute to a better understanding of the overall stability of ecosystems in the future.…”
Section: Discussionmentioning
confidence: 99%
“…α functional stability at the plot scale was defined as the biomass‐weighted average of the temporal stability of each plot, and γ functional stability at the transect scale was defined as the temporal stability of the total community biomass of the 5 plots along a transect (Wang et al, 2019). The α compositional stability at the plot scale was quantified by one minus the mean Euclidean distance from each plot in each year to its centroid over 7 years (2003–2010, with the exception of 2005), with the distance calculated based on the Bray–Curtis dissimilarity between two communities of the same plot in each year and then averaged at the transect level (Xu et al, 2022). γ compositional stability at the transect scale was quantified by one minus the mean Euclidean distance from each transect in each year to its 7‐year (2003–2010, with the exception of 2005) transect centroid, with distance calculated based on the Bray–Curtis dissimilarity among communities of the same transect.…”
Section: Methodsmentioning
confidence: 99%
“…The expected rise in atmospheric greenhouse gases and associated warming trends in the coming decades will lead to increases in drought frequency and duration in many regions (Bradford et al, 2020). This predicted intensification of drought has the potential to decrease primary production and biodiversity, and alter community composition, with immediate and potentially long‐lasting post‐drought impacts on ecosystem function and stability at regional and global scales (He et al, 2022; Knapp et al, 2008; Luo et al, 2023; Xu, Yang, et al, 2022). Indeed, several broad‐scale analyses have found that water‐limited ecosystems such as grasslands are especially vulnerable to drought both during and after these events end (Knapp et al, 2015; Maurer et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, several broad‐scale analyses have found that water‐limited ecosystems such as grasslands are especially vulnerable to drought both during and after these events end (Knapp et al, 2015; Maurer et al, 2020). Determining how and why ecosystem stability is altered by both drought and post‐drought effects may improve our ability to predict how future changes in precipitation will impact ecosystem structure and functions (Broderick et al, 2022; Xu, Yang, et al, 2022). Yet, most studies that model the influence of climate change have focused on ecosystem function and stability during drought periods, whereas ecosystem stability during post‐drought periods has received much less attention (de Bello et al, 2021; He et al, 2022; Matos et al, 2020), with even less research on the mechanistic pathways behind these responses.…”
Section: Introductionmentioning
confidence: 99%